THE INVESTIGATION OF FACTORS AFFECTING TIMELINESS OF FINANCIAL STATEMENTS: EVIDENCE FROM TURKEY - Ahmet Özcan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In the current economic environment, thetimeliness of corporate financial reporting is one of the important factorsthat have impact on the efficiency of financial markets. Delay in disclosure offinancial statements prominently decreases the efficiency of financial markets.This study aims to analyze factors that influence timely corporate financialreporting by using a sample that includes 90 manufacturing firms listed onBorsa Istanbul over the period of 2014-2017. The results of regression analysisreveal that firm size, type of audit firm, board independency, profitabilityand leverage significantly affect the timeliness of financial statements. Thefindings of empirical analysis provide vital implications for regulatoryagencies.